Modeling of ingestion of flammable gas mixture by a gas turbine engine compressor using OpenFoam - Chow, Jian Yong (2016)
This report summaries the results of computational fluid dynamic simulations by using an open-source software, OpenFOAM in modeling of a gas turbine compressor. The main objective is to simulate the combustion of methane gas with air in the compressor as close as possible to the estimated data. Different turbulence models were revised and available in OpenFOAM. Initial trials were performed with different types of boundary conditions to simulate the flow as close to the data as plausible. The reduced chemical kinetic model was introduced and used for the air-methane combustion. Three different types of momentum source methods have been also implemented to model the effect of the compressor.